The terrestrial isopod symbiont ‘Candidatus Hepatincola porcellionum’ is a potential nutrient scavenger related to Holosporales symbionts of protists - Jessica Dittmer; Marius Bredon; Bouziane Moumen; Maryline Raimond; Pierre Grève; Didier Bouchon (ISME Communications, 2023)
Abstract The order Holosporales (Alphaproteobacteria) encompasses obligate intracellular bacterial symbionts of diverse Eukaryotes. These bacteria have highly streamlined genomes and can have negative fitness effects on the host. Herein, we present a comparative analysis of the first genome sequences of ‘Ca. Hepatincola porcellionum’, a facultative symbiont occurring extracellularly in the midgut glands of terrestrial isopods. Using a combination of long-read and short-read sequencing, we obtained the complete circular genomes of two Hepatincola strains and an additional metagenome-assembled draft genome. Phylogenomic analysis validated its phylogenetic position as an early-branching family-level clade relative to all other established Holosporales families associated with protists. A 16S rRNA gene survey revealed that this new family encompasses diverse bacteria associated with both marine and terrestrial host species, which expands the host range of Holosporales bacteria from protists to several phyla of the Ecdysozoa (Arthropoda and Priapulida). Hepatincola has a highly streamlined genome with reduced metabolic and biosynthetic capacities as well as a large repertoire of transmembrane transporters. This suggests that this symbiont is rather a nutrient scavenger than a nutrient provider for the host, likely benefitting from a nutrient-rich environment to import all necessary metabolites and precursors. Hepatincola further possesses a different set of bacterial secretion systems compared to protist-associated Holosporales, suggesting different host-symbiont interactions depending on the host organism.